2021
DOI: 10.2147/opth.s300886
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sodium Iodide on Stromal Loading, Distribution and Degradation of Riboflavin in a Rabbit Model of Transepithelial Corneal Crosslinking

Abstract: Purpose: To evaluate effects of sodium iodide (NaI) on riboflavin concentration in corneal stroma before and during ultraviolet A (UVA) light exposure using a novel transepithelial corneal collagen crosslinking (CXL) procedure (EpiSmart CXL system, CXL Ophthalmics, Encinitas CA). Methods: Riboflavin solutions with NaI (Ribostat, CXL Ophthalmics, Encinitas CA) and without NaI were used for CXL in rabbits using EpiSmart. A pilot study determined sufficient riboflavin loading time. Four rabbits were dosed and mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“… 22 It was also confirmed in vivo that the riboflavin solution containing iodide promotes persistence of riboflavin throughout UVA exposure. 21 A previous report of clinical application demonstrated significant improvements in visual acuity and corneal topography with a low rate of adverse events. 16 …”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“… 22 It was also confirmed in vivo that the riboflavin solution containing iodide promotes persistence of riboflavin throughout UVA exposure. 21 A previous report of clinical application demonstrated significant improvements in visual acuity and corneal topography with a low rate of adverse events. 16 …”
Section: Discussionmentioning
confidence: 95%
“…The epithelium-on treatment protocol has been described in previous publications. 16 , 20 , 21 Corneal anesthesia was obtained with 2–3 drops of topical proparacaine (0.5%, Alcon Laboratories, Fort Worth TX). At the slit lamp, a proprietary, non-disruptive sponge wand (EpiPrep ® CXL Ophthalmics, Encinitas, CA) was used to modify surface lipids in the tear film.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Subjects were treated with the EpiSmart system (CXL Ophthalmics, LLC), comprising ophthalmic sponges for the preparation of the cornea and drug delivery (EpiPrep; CXL Ophthalmics), 10 , 18 riboflavin 5′-phosphate and sodium iodide (0.5%/0.015%) ophthalmic solution (RiboStat; CXL Ophthalmics), 18 , 19 and an ultraviolet-A illuminator (CXL Ophthalmics) that delivers ultraviolet light (365 nm wavelength) in a 12-mm diameter circular pattern onto the corneas in 15-second on/15-second off cycles. 10 , 18 , 19 The technique was as previously described by Stulting et al 10 Proparacaine anesthetic was instilled in the eye(s) immediately before treatment. The sterile ophthalmic sponge wand was hydrated with proparacaine solution and used to remove lipids, mucus, and any other debris from the surface of the cornea without disruption of the epithelium.…”
Section: Methodsmentioning
confidence: 99%
“…[15][16][17] The EpiSmart epi-on crosslinking procedure (CXL Ophthalmics, Encinitas, CA) has been shown in animal models to obtain adequate stromal riboflavin levels across an intact epithelium 18 and to maintain a sustained riboflavin concentration without supplemental riboflavin drops throughout ultraviolet-A (UVA) exposure. 19 Stulting et al 10 reported on 308 patients with keratoconus treated with EpiSmart who showed improvements in vision and improvements in keratometric end points, each sustained over 24 months. This same report also demonstrated significant improvement in coma which can account for some of the significant visual improvements seen.…”
mentioning
confidence: 99%